The Mechanism of TNF-α-Mediated Accumulation of Phosphorylated Tau Protein and Its Modulation by Propofol in Primary Mouse Hippocampal Neurons: Role of Mitophagy, NLRP3, and p62/Keap1/Nrf2 Pathway. (12th August 2022) - Zhang, Lin; Song, Hong; Ding, Jie; Wang, Dong-jie; Zhu, Shi-peng; Liu, Chi; Jin, Xian; Chen, Jia-wei
Abstract : Background . Neuroinflammation-induced phosphorylated Tau (p-Tau) deposition in central nervous system contributes to neurodegenerative disorders. Propofol possesses neuroprotective properties. We investigated its impacts on tumor necrosis factor- α (TNF- α )-mediated p-Tau deposition in neurons. Methods . Mouse hippocampal neurons were exposed to propofol followed by TNF- α . Cell viability, p-Tau, mitophagy, reactive oxygen species (ROS), NOD-like receptor protein 3 (NLRP3), antioxidant enzymes, and p62/Keap1/Nrf2 pathway were investigated. Results . TNF- α promoted p-Tau accumulation in a concentration- and time-dependent manner. TNF- α (20 ng/mL, 4 h) inhibited mitophagy while increased ROS accumulation and NLRP3 activation. It also induced glycogen synthase kinase-3 β (GSK3 β ) while inhibited protein phosphatase 2A (PP2A) phosphorylation. All these effects were attenuated by 25  μ M propofol. In addition, TNF- α -induced p-Tau accumulation was attenuated by ROS scavenger, NLRP3 inhibitor, GSK3 β inhibitor, or PP2A activator. Besides, compared with control neurons, 100  μ M propofol decreased p-Tau accumulation. It also decreased ROS and NLRP3 activation, modulated GSK3 β /PP2A phosphorylation, leaving mitophagy unchanged. Further, 100  μ M propofol induced p62 expression, reduced Keap1 expression, triggered the nuclear translocation of Nrf2, and upregulated superoxide dismutase (SOD) and heme oxygenase-1 (HO-1) expression, which was abolished by p62 knockdown, Keap1 overexpression, or Nrf2 inhibitor. Consistently, the inhibitory effect of 100  μ M propofol on ROS and p-Tau accumulation was mitigated by p62 knockdown, Keap1 overexpression, or Nrf2 inhibitor. Conclusions . In hippocampal neurons, TNF- α inhibited mitophagy, caused oxidative stress and NLRP3 activation, leading to GSK3 β /PP2A-dependent Tau phosphorylation. Propofol may reduce p-Tau accumulation by reversing mitophagy and oxidative stress-related events. Besides, propofol may reduce p-Tau accumulation by modulating SOD and HO-1 expression through p62/Keap1/Nrf2 pathway.